Systematic investigation of chemical abundances derived using IR spectra obtained with GIANO* - Caffau, Elisabetta; Ludwig, Hans-Günter (Astronomy and astrophysics, 2019)
Context. Detailed chemical abundances of Galactic stars are needed in order to improve our knowledge of the formation and evolution of our galaxy, the Milky Way.Aims. We took advantage of the GIANO archive spectra to select a sample of Galactic disc stars in order to derive their chemical inventory and to compare the abundances we derived from these infrared spectra to the chemical pattern derived from optical spectra.Methods. We analysed high-quality spectra of 40 stars observed with GIANO. We derived the stellar parameters from the photometry and the Gaia data-release 2 (DR2) parallax; the chemical abundances were derived with the code MyGIsFOS. For a subsample of stars we compared the chemical pattern derived from the GIANO spectra with the abundances derived from optical spectra. We derived P abundances for all 40 stars, increasing the number of Galactic stars for which phosphorus abundance is known.Results. We could derive abundances of 14 elements, 8 of which are also derived from optical spectra. The comparison of the abundances derived from infrared and optical spectra is very good. The chemical pattern of these stars is the one expected for Galactic disc stars and is in agreement with the results from the literature.Conclusions. GIANO is providing the astronomical community with an extremely useful instrument, able to produce spectra with high resolution and a wide wavelength range in the infrared.